A Bibliometric Analysis of Marine Tourism In 2023 - Hordembun, Dafrosa; Sofie, Varsyah Indriana; Pradini, Gagih; Agustiani, Fitri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Marine tourism research is not the same as the results of research on marine tourism that have been widely researched by other researchers, it is a novelty with previous works. This study aims to identify current marine tourism trends such as sources, authors, and types of documents. Bibliometric analysis was used to analyze 60 articles from Google Scholar published in 2023. Marine Tourism is the main keyword used in article titles, and abstracts to get metadata taken from the Google Scholar bibliographic database. The tools used in analyzing bibliometrics are Microsoft Excel used to analyze frequency, Vos-Viewer for data visualization and Harzing's Publish or Perish used for citation metrics. This study's results show that most related articles are published in scientific journals compared to others. Related articles published in scientific journals have obtained the highest citations compared to others. Articles are also found in English. Based on network visualization the most dominant term (often appears) is "Marine Tourism" which is closely related to Tourism and study. When viewed from the Overlay Visualization the topic 'Marine Tourism' shows the latest trends in research.